Beberapa Pandangan Tentang Guru Sebagai Pendidik - Suharmoko Suharmoko (LPPM IAIN Sorong, 2019)
This paper aims to convey some views on the position of the teacher as an educator. This is seen as a highly important case because in an implementation of education system, the teacher occupies the leading position in education itself. However, it needs to be realized that in teacher recruitment, there are several requirements that need to be completed. In this paper also presented some insights from various perspectives which underlie the teacher's view as an educator. All of which contain ideas of direction and guidance. In this paper also discusses the teacher typology which includes teacher requirements, teacher nature, and teacher tasks. In addition to the teacher typology that must be considered, an educational institution needs to form a code of ethics that is used as a guide by teachers who educate students at the institution. So that there is a need to standardize the minimum requirements of teachers, such as: believing and devoting to Allah, being mature, knowledgeable, physically and spiritually healthy, noble, and able to educate in a broad sense. Teacher is expected to concern of the awareness of responsibility to maximize the potential of students to become individuals who have noble character and personality, maturity, intelligence (intellectual, emotional and spiritual) who are more mature and can be responsible.